Othering of Women in The Wasted Vigil: A Muted Group Theory Perspective - Muhammad Uzair Jan; Riaz Ullah; Muhammad Hamza; Ishtiaq Muhammad (University of Chitral Journal of Linguistics and Literature)
In this research article, the Othering idea of Women is focused on The Wasted Vigil (2008), from the perspective of Muted Group and Patriarchy Theories. In this article, qualitative research method is used. The objective aims to scrutinize the aspects of gendered otherness and social marginalization. MGT, pioneered by scholars like Ardener and later elaborated by Kramarae, serves as a crucial lens through which the silencing of women was examined. Simultaneously, the patriarchal tenets discussed by Connell and Hooks offer a space to explore the systemic hierarchy that marginalizes women. The findings reveal that the women characters in The Wasted Vigil (2008) depict muted groups whose attempts at resistance were both courageous and paradoxically constrained by patriarchal discourse. Secondly, the portrayal of oppressive factors ranged from physical violence to institutional forms of control. Whereas the resistance’s acts were observed, they often fell within the margins established by the male’s dominant society, thereby questioning the effectiveness of such resistance.